Death, life, and religious change in Scottish towns c.1350-1560 - Cowan, Mairi, 1974- (Manchester University Press, 2012)
This title examines lay religious culture in Scottish towns between the Black Death and the Protestant Reformation: what the living did to influence the dead and vice versa; considers both continuities and changes, highlighting the Catholic Reform movement that reached Scottish towns before the Protestant Reformation took hold.